A Comparison of Complex Lattice Reduction Algorithms for MIMO Detection - Barbero, L.G.; Ratnarajah, T.; Cowan, C. (2008 IEEE International Conference on Acoustics, Speech and Signal Processing, 2008)
The performance and complexity of two complex lattice reduction (LR) algorithms used in multiple input-multiple output (MIMO) detection are compared in this paper. The Seysen's Algorithm (SA) has been previously proposed as a low-complexity alternative to the real version of the Lenstra-Lenstra-Lovasz (LLL) algorithm while providing a better performance in LR-aided linear detectors. However, this paper shows that the SA has a higher complexity than the complex version of the LLL algorithm, due to its more computationally intensive preprocessing stage and its higher complexity per iteration. In addition, both the SA and the complex LLL algorithm provide practically the same performance when used in LR-aided successive interference cancellation (SIC) detectors.